(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the significance of social collaboration in inclusive education, with a particular focus on the shared responsibility of parents, educators, and society in ensuring equal opportunities for children with special needs. Inclusive education requires not only the presence of children with diverse abilities in mainstream schools but also the creation of supportive environments where they can learn, develop, and interact effectively. The research emphasizes the crucial role of parents in fostering early adaptation, the responsibilities of teachers in applying innovative pedagogical approaches, and the importance of community awareness and support in eliminating social barriers. By analyzing both theoretical perspectives and practical approaches, this study highlights the necessity of building strong partnerships among families, schools, and wider society to guarantee sustainable success in inclusive practices. The findings suggest that the effective integration of children with special needs depends on collective efforts, where every stakeholder contributes to creating an equitable and respectful educational environment.